Pandangan Islam Terhadap Pluralisme dan Multikulturalisme: Perspektif Surah Al-Hujurat Ayat 13 - Firdaus, Naufal; Azizah, Sofa Sofiatul; Assondani, Muhammad Mufri Najmul Umam (JSPH : Jurnal Sosial Politik Humaniora, 2025)
This article examines Islam's perspective on pluralism and multiculturalism through the lens of Surah Al-Hujurat, verse 13. This verse emphasizes the significance of human diversity, created in various tribes and nations, as a manifestation of Allah's greatness and a means to foster mutual understanding. Employing a thematic exegesis approach, the study analyzes how Islamic principles uphold diversity, justice, and tolerance as essential elements for building social harmony. The findings reveal that Islam acknowledges plurality as a natural aspect of human existence and emphasizes universal brotherhood that transcends ethnic, cultural, and religious boundaries. This verse provides an ethical foundation for strengthening intercultural interactions based on respect and mutual comprehension, positioning pluralism and multiculturalism as opportunities to enhance human relationships. These insights contribute to contemporary discourse on interfaith dialogue and managing diversity in multicultural societies.